Strength training induces greater increase in handgrip strength than wrestling training per se - Karatrantou, K.; Katsoula, C.; Tsiakaras, N.; Ioakimidis, P.; Gerodimos, V. (International Journal of Sports Medicine, 2020)
This study investigated the effectiveness of a specialized strength training program on maximal handgrip strength in young wrestlers. 72 young wrestlers (36 children: 8-10 years-old and 36 adolescents:13-15 years-old) participated in the present study. Both age-categories were assigned into a training group (18 children and 18 adolescents) and a control group (18 children and 18 adolescents). The training groups, in conjunction with the wrestling training performed a 4-month (2 sessions/week) specialized handgrip training program. Maximal handgrip strength was evaluated pre, at the intermediate (2 months) and at the completion of the program (4 months). Maximal handgrip strength values increased during the intermediate and post-training measurements compared to pre-training measurement in training and control groups (p<0.001). No significant differences were observed on pre-training and intermediate measurements between groups, while significant differences were observed during the post-training measurement. Training group exhibited significantly (p<0.01) greater maximal handgrip strength values than the control group irrespective of age-category and hand-preference. A 4-month handgrip strength training program, incorporated into the conventional wrestling training, provokes greater adaptations in maximal handgrip strength than the wrestling training per se. For greater handgrip training adaptations are required more than 14 specialized handgrip training-sessions.